Determination of the role of serum alpha 1 anti-trypsin protein levels in oral squamous cell carcinoma Patients and in healthy snuff users and non-users - Tariq, Faizan; Iqbal, Fatima; Nausheen, Tehmina; Khan, Hayatullah; Gul, Ambreen; Khan, Abbas Saleem (International Journal of Pathology, 2025)
Background: Among head & neck cancers, oral squamous cell carcinoma (OSCC) is the most common malignant neoplasm of lip and oral cavity. The serum analysis of different biomarkers including Alpha 1 antitrypsin, showed various biochemical changes which is considered to be significant in early intervention leading to an increase in survival rate. The objective of our study is to determine serum alpha 1 anti-trypsin (AAT) protein levels in oral squamous cell carcinoma patients and in healthy individuals (tobacco users and non-users) to detect the likelihood of OSCC development. The rationale of the study is that the early detection of OSCC helps in early intervention which results in an increase in the survival rate. Methods: This cross-sectional study was conducted from June 2023 to October 2023 at the Chemical Pathology Department of Mercy Teaching Hospital, Peshawar and the Department of Oral Pathology, Peshawar Dental College, Peshawar. A total of 90 subjects were included in the study, divided into 3 groups: 30 subjects having OSCC form Group A. Group B comprised of subjects who were healthy tobacco users. Group C comprised of subjects who were healthy and didn’t use tobacco. The evaluation of samples was carried out with alpha1antitrypsin ELISA kit and statistical analysis was performed using SPSS version 19. Results: A slight rise regarding serum levels was seen for AAT antibody in Group B (healthy individuals tobacco users) (2.96) in comparison to Group C (healthy individuals’ tobacco non-users) (2.32). Also, AAT levels were expressed in serum of OSCC patients (2.53). Conclusion: AAT may be used as a diagnostic marker for OSCC.